2017
DOI: 10.1002/aic.15804
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic programming models for optimal shale well development and refracturing planning under uncertainty

Abstract: In this work we present an optimization framework for shale gas well development and refracturing planning. This problem is concerned with if and when a new shale gas well should be drilled at a prospective location, and whether or not it should be refractured over its lifespan. We account for exogenous gas price uncertainty and endogenous well performance uncertainty. We propose a mixed‐integer linear, two‐stage stochastic programming model embedded in a moving horizon strategy to dynamically solve the planni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Tavallali et al [130] also combine well placement and control. The results of both Drouven et al [129] and Tavallali et al [130] highlight valuable insight into the well placement and control interrelationship obtained by combining well placement and control optimization. Adjoint optimization is finding increased use in coupled well placement and injection optimization.…”
Section: Coupled Well Placement and Well Control Optimizationmentioning
confidence: 98%
See 1 more Smart Citation
“…Tavallali et al [130] also combine well placement and control. The results of both Drouven et al [129] and Tavallali et al [130] highlight valuable insight into the well placement and control interrelationship obtained by combining well placement and control optimization. Adjoint optimization is finding increased use in coupled well placement and injection optimization.…”
Section: Coupled Well Placement and Well Control Optimizationmentioning
confidence: 98%
“…They found that profitability of investments could be significantly improved by combining well location and surface gathering considerations. In recent work Drouven et al [129] optimize shell gas well placement and refracturing scheduling together. Tavallali et al [130] also combine well placement and control.…”
Section: Coupled Well Placement and Well Control Optimizationmentioning
confidence: 99%
“…The models for shale gas development that consider uncertainty are relatively few. Drouven et al apply two‐stage stochastic programming in a moving horizon approach for optimal shale well development and refracturing planning under exogenous gas price uncertainty and endogenous well performance uncertainty. Gao and You develop a two‐stage stochastic mixed integer linear fractional programming (SMILFP) model to optimize the levelized cost of energy generated from shale gas under uncertainty of estimated ultimate recovery (EUR).…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, data driven or simulation based tools have been developed for the economic assessment of natural gas production from shale gas plays, including considerations regarding the optimal well‐pad layout . Furthermore, supply chain optimization models have also been proposed for shale gas development, for the corresponding water management problems, and for the integrated shale gas development and water management problem . Some of the aforementioned frameworks consider uncertainty in freshwater availability, water demand for hydraulic fracturing as well as wastewater production, gas production, and gas prices .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, supply chain optimization models have also been proposed for shale gas development, for the corresponding water management problems, and for the integrated shale gas development and water management problem . Some of the aforementioned frameworks consider uncertainty in freshwater availability, water demand for hydraulic fracturing as well as wastewater production, gas production, and gas prices . Although significant progress has been achieved in the modeling, simulation, and optimization of shale gas development, further research efforts are needed towards the development of integrated supply chain models that deal with the uncertainties in a systematic way.…”
Section: Introductionmentioning
confidence: 99%